Characterization of permissive and non-permissive peptide insertion sites in chloramphenicol acetyltransferase. (December 2020) - Goodale, Andrew; Michailidis, Fanourios; Watts, Rachel; Chok, Shi Chen; Hayes, Finbarr
Abstract: The growing prevalence of antibiotic resistance in numerous pathogenic bacteria is a major public health concern and urgently requires the development of new therapeutic approaches. Multidrug resistant species that remain sensitive to chloramphenicol (CAM) treatment have engendered renewed interest in using this drug as a modern day antimicrobial agent. High-level resistance to CAM commonly is mediated by chloramphenicol acetyltransferase (CAT) which catalyzes the acetylation of CAM and renders the drug inactive. Of the three main types (CATI, CATII and CATIII ), CATI is of broad clinical significance. Despite this importance, understanding of the catalytic mechanism of CATI largely is extrapolated from studies of CATIII . Here, pentapeptide scanning mutagenesis was used to generate a library of random insertions in CATI to gain a better understanding of structure-function relationships in the enzyme. Pentapeptide insertions in secondary structure elements which contain residues that form part of the CATI active site abolished CAM resistance in Escherichia coli . Insertions in secondary structures that have key roles in protein folding and CAM binding led to a reduction in resistance. In contrast, insertions in loop regions between the major secondary structure features exerted modest, if any, effects on CAM resistance. The analysis pinpoints regions of CATI that may serve as targets for the design of novel inhibitors that prevent the spread of CAM-resistant pathogens thereby enabling the drug to be re-deployed as a broad range antimicrobial agent. Moreover, regions of CATI that are tolerant of insertions may be suitable for the construction of bifunctional enzymes in which peptides, mini-proteins or amino acid tags are introduced at the permissive sites. Highlights: Antibiotic resistance in bacteria is a major public health concern. Chloramphenicol resistance is mediated by chloramphenicol acetyltransferase (CAT). Insertions in an archetypal CAT were generated by pentapeptide scanning mutagenesis. Regions of CAT were identified that may be targets for novel inhibitors. Sites in CAT that tolerate insertions may be used in bifunctional enzyme design.